2014
DOI: 10.1016/j.neo.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

5-aza-2′-deoxycytidine-mediated c-myc Down-regulation Triggers Telomere-dependent Senescence by Regulating Human Telomerase Reverse Transcriptase in Chronic Myeloid Leukemia

Abstract: Increased proliferation rates as well as resistance to apoptosis are considered major obstacles for the treatment of patients with chronic myelogenous leukemia (CML), thus highlighting the need for novel therapeutic approaches. Since senescence has been recognized as a physiological barrier against tumorigenesis, senescence-based therapy could represent a new strategy against CML. DNA demethylating agent 5-aza-2′-deoxycytidine (DAC) was reported to induce cellular senescence but underlying mechanisms remain to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 55 publications
3
35
0
Order By: Relevance
“…Recently, 5-aza was shown to decrease telomere length and reduce telomerase activity in chronic leukemia cell lines. 37 This further corroborates our conclusion that 5-aza mimics natural senescence caused by telomere shortening.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Recently, 5-aza was shown to decrease telomere length and reduce telomerase activity in chronic leukemia cell lines. 37 This further corroborates our conclusion that 5-aza mimics natural senescence caused by telomere shortening.…”
Section: Discussionsupporting
confidence: 87%
“…Cells were treated for 2 hours (MDAH041) or 1.5 hours (087-N, 087-1 and 172) at 37 C, and were then washed with PBS and growth media was replenished. Cells were grown at 37 C for 5 days before harvest for RNA or protein.…”
Section: Methodsmentioning
confidence: 99%
“…[11, 2530] Published data have revealed that the effect of DNMTIs on TERT expression in malignant cells varies dependent on cell types. [25, 31–36] Importantly, as TERT is involved in chemo- and radio-resistance of malignant cells, [2224] it is critical to elucidate whether TERT is capable of protecting DNMTI-mediated apoptosis. Moreover, it is currently unclear whether DNMT inhibition affects telomere function in AML cells.…”
Section: Introductionmentioning
confidence: 99%
“…[8] DAC was also able to decrease telomere length, to reduce telomerase activity and to decrease human telomerase reverse transcriptase (hTERT) expression through decreased binding of c-myc to the hTERT promoter. [9] Then, it induces senescence in CML cell lines. In Kantarjian's report, [10] 130 patients with CML were treated with high dose of DAC.…”
Section: Discussionmentioning
confidence: 99%